Solution processes for ultrabroadband and omnidirectional graded-index glass lenses with near-zero reflectivity in high concentration photovoltaics - He, Junwen; Yao, Yuan; Lee, Kyu Tae; Hong, Nina; Fisher, Brent; Bahabry, Rabab R.; Lee, Jung Woo; Kim, Jeonghyun; Han, Seungyong; Kalidindi, Sanjay V.; Kim, Jae Hwan; Kim, Sung Bong; et al. (Scientific Reports, 2018)
Concentrator photovoltaic (CPV) systems, where incident direct solar radiation is tightly concentrated onto high-efficiency multi-junction solar cells by geometric optical elements, exhibit the highest efficiencies in converting the sun’s energy into electric power. Their energy conversion efficiencies are greatly limited, however, due to Fresnel reflection losses occurring at three air/optics interfaces in the most sophisticated dual-stage CPV platforms. This paper describes a facile one-step wet-etching process to create a nanoporous surface with a graded-index profile on both flat and curved glasses, with capabilities of achieving ~99% average transmission efficiency in a wide wavelength range from 380 nm to 1.3 µm and for a wide range of incident angles up to ±40° regardless of the polarization state of incident sunlight. The simplicity of the etching process remarkably increases their versatility in various optical elements that require unconventional form factors such as Fresnel lenses and microlens arrays, and/or demanding curvatures along with much reduced dimensions such as ball lenses. Etched glass surfaces on two-stage optical concentrating systems yield enhancements in total optical transmission efficiencies by 13.8% and in the photocurrent by 14.3%, as experimentally determined by measurements on microscale triple-junction solar cells. The presented strategy can be widely adapted in a variety of applications such as image sensors, display systems, and other optoelectronic devices.